Misplaced Intrauterine Contraceptive Device (IUCD) Presentation, Diagnosis and Management - Shaikh, Farhana; Parveen, Naheed; Mohammad, Agha Taj (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the Presentation, Diagnosis and Management of Misplaced Intrauterine Contraceptive Device (IUCD). METHEDOLOGY: It was an observational retrospective study carried out in the obstetrics and gynecology Unit II, Liaquat University of Medical and Health Sciences Jamshoro from January 2016 to December 2017. Twenty patients enrolled were presented / referred with missing IUCD thread or misplaced IUCD . Performa was designed which contained age, parity, whom inserted , place and duration of IUCD insertion and clinical presentation. Other parameters of Performa contained diagnostic tools for localization of IUCD, and procedure for retrieval of IUCD. RESULTS: During study period 391 patients were gynae admissions out of them 20 had misplaced IUCD so frequency of misplaced IUCD was 5.11%. 13(65%) patients were grand multipara, 12(60%) were 26-40 years of age, 11(55%) of women presented with complain of loss string of IUCD, lower abdominal pain in 3(15%), menstrual problem in 5(25%), and pregnancy with IUCD in 1(5%). In 8(40%) women IUCD was removed with curettage and retrieval forceps, 5(25%) of patients IUCD was removed directly from cervical canal. In 7(35%) laparotomy was performed for IUCD removal. CONCLUSION: IUCD is mostly inserted by lady health workers and family planning staff without prior assessment and training. Therefore proper training program should be arrange for community health care professionals to provide better, safe and effective family planning services for community and reduce the occurance of misplaced IUCD or perforation of uterus and it sequel.